Utilization of Moringa oleifera leaf meal as a protein source in diets for Cirrhinus mrigala: effects on growth, body composition, and hematology - Faisal, Muhammad; Hussain, Syed Makhdoom; Sarker, Pallab K.; Ali, Shafaqat; Al-Ghanim, Khalid A.; Yousaf, Zeeshan (Frontiers in Sustainable Food Systems, 2024)
In the current study, Cirrhinus mrigala was used as an animal model to investigate the impacts of Moringa oleifera leaf meal (MOLM) on their overall performance reared in six earthen ponds. In this study, fishmeal (FM) was substituted with MOLM at various levels in the diet: 0% (control), 10%, 15%, 20%, 25%, and 30%, for a six-month feeding trial. A total of 270 fish with 15 fingerlings (15.31±0.12 g/fish) stocked in each of the six earthen ponds in triplicates. When compared to other experimental and control groups, analyses revealed that fish given a diet having 10% MOLM had the highest growth performance (final weight: 422.32 g, weight gain: 406.97 g). Fingerlings fed a diet which substituted with 10% of FM with MOLM showed the greatest results for body composition (crude protein: 19.31%; crude fat: 3.01%). The results of hematology i.e., WBCs: 7.65×10 3 mm -3 ,